Ranging behavior of Rattus novergicus in wet market Pasar Jalan Othman, Petaling Jaya - Wahab, Muhammad Zulhafizi (2016)
The rodents are the largest group of mammals that include rats, squirrels and porcupine. They are very successful and occupy every niche of the environment whether natural or modified. Rattus spp. are the source of a number of zoonotic pathogens responsible for human diseases and mortality. Recently cases of leptospirosis that are reported is increasing. Rattus norvegicus has over recent decades have dominated and become fully adapted to urban areas. The objective of this study is to understand the behavior of R. norvegicus. One aspect of behavioral study is the ranging behavior and pattern of habitat use. Radio telemetry was used in this study to map the home range and to investigate the activity pattern of R. norvegicus. 3 rats (1 mature male and 2 immature male) in and around the wet market of Pasar Besar Jalan Othman were captured using live trap cage and were anaesthetized for identification purpose. Radio transmitters of specific frequencies were attached to 2 rats (immature males). Radio tagged rats were followed from 2100 hrs to 0000 hrs or 4-5 hours over five days to mark the locations visited and extant of the area covered. Approximate locations of each rat were determined by triangulation method. The home range size and the core area were estimated using MCP (Minimum Convex polygon) and Kernel method. The home ranges analyses were calculated using the software Biotas of the Ecological Software Solutions Inc. The home range size of rat was influenced by the dissemination and the abundance of food or population density. The core area size was influenced by greater exploration get the desired food or favorite feeding spot. This study also showed that R. novergicus is more active early in the night and late night.